To solve the equation \(9x + 16 = 6x + 1\), we can follow these steps:
-
Isolate the variable \(x\) by getting all terms involving \(x\) on one side of the equation and constant terms on the other side.
Subtract \(6x\) from both sides: \[ 9x - 6x + 16 = 1 \] Simplifying this gives: \[ 3x + 16 = 1 \]
-
Next, subtract \(16\) from both sides: \[ 3x = 1 - 16 \] Simplifying this gives: \[ 3x = -15 \]
-
Finally, divide both sides by \(3\): \[ x = \frac{-15}{3} = -5 \]
Thus, the solution is: \[ \boxed{-5} \]
So the correct choice is:
x = −5 (x equals negative 5).